FUNGSI KOGNITIF PADA PASIEN TUMOR OTAK METASTASIS PASCA RADIASI WHOLE BRAIN RADIOTHERAPY DI DUA RS RUJUKAN KANKER INDONESIA - Rahmi Ardhini,* Tiara Aninditha,** Rini Andriani,*** Henry Riyanto Sofyan** (NEURONA, 2020)
METASTASES REPRESENT ONE OF THE MOST COMMON NEUROLOGICAL COMPLICATIONS OF SYSTEMIC CANCER WITH AN INCIDENCE WAS ABOUT 40 WHOLE BRAIN RADIOTHERAPY WBRT IS A STANDARD TREATMENT TO REDUCE TUMOR VOLUME AND INCREASING PATIENTS SURVIVAL BUT WBRT HAS A SIDE EFFECTS DUE TO RADIATION EXPOSURE TO THE BRAIN PARENCHYMA INCLUDING COGNITIVE IMPAIRMENT